Pengaruh Kinerja Keuangan saat Merger terhadap Penilaian Perusahaan pada Bank Syariah Indonesia yang Terdaftar di Bursa Efek Indonesia - Dilla Candra Hapsari; Purwohandoko Purwohandoko (Jurnal Ilmu Manajemen, 2022)
This study aims to determine the effect of financial performance resulting from return on assets, capital adequacy ratio, non-performing financing, and loan to deposit ratio on company valuation during the merger. This quantitative research uses a causal approach. The research sample uses all members of the population. There are 4 independent variables used, namely return on asset, capital adequacy ratio, non performing financing, and loan to deposit ratio. While the dependent variable is the value of the company (price book value). For data analysis used in this study is multiple linear regression analysis. The results of the analysis of the study are that ROA has a negative effect on PBV, CAR has a positive effect on PBV, and NPF and LDR have a negative effect on PBV. To increase the value of the company, banks must pay attention to financial performance every year. The implications of the company are suggested to be able to maintain and improve the company's financial performance with the aim of increasing the value of the company and attracting public interest in investing.